(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the success of tourism destinations in Pandak Gede Village in Kediri District, Tabanan Regency, Bali. The research methodology uses a qualitative descriptive approach, namely a research method based on philosophy used to research the condition of natural objects. With data collection techniques through observation, interviews, and documentation. Supported by data analysis techniques using the Guttman scale, which is processed using the descriptive percentage analysis method. The informants in this study were the Head of Pandak Gede Village, the Head of Pandak Gede Traditional Village, the community, and tourists who were selected by purposive sampling. The result of the study showed that the assessment of the success of Pandak Gede Village as a tourism destination was obtained by 80% of the 10As of Successful Tourism Destination assessment. The result of the study revealed that with active participation from the community and government support, the potential for the success of Pandak Gede Village as a tourism destination is very high, and with good preservation of cultural heritage, it can be used as a cultural tourism attraction. In conclusion, Pandak Gede Village has great potential as a cultural tourism destination that still maintains existing cultural values. To increase the exposure of Pandak Gede Village as a tourism destination, promotion and marketing need to be implemented so that it can be known at national and international levels.